Skeletal muscle mitochondrial oxidative phosphorylation function in idiopathic pulmonary arterial hypertension: in vivo and in vitro study. (May 2018) - Sithamparanathan, Sasiharan; Rocha, Mariana C.; Parikh, Jehill D.; Rygiel, Karolina A.; Falkous, Gavin; Grady, John P.; Hollingsworth, Kieren G.; Trenell, Michael I.; Taylor, Robert W.; Turnbull, Doug M.; Gorman, Gráinne S.; Corris, Paul A.
Mitochondrial dysfunction within the pulmonary vessels has been shown to contribute to the pathology of idiopathic pulmonary arterial hypertension (IPAH). We investigated the hypothesis of whether impaired exercise capacity observed in IPAH patients is in part due to primary mitochondrial oxidative phosphorylation (OXPHOS) dysfunction in skeletal muscle. This could lead to potentially new avenues of treatment beyond targeting the pulmonary vessels. Nine clinically stable participants with IPAH underwent cardiopulmonary exercise testing, in vivo and in vitro assessment of mitochondrial function by 31 P-magnetic resonance spectroscopy ( 31 P-MRS) and laboratory muscle biopsy analysis. 31 P-MRS showed abnormal skeletal muscle bioenergetics with prolonged recovery times of phosphocreatine and abnormal muscle pH handling. Histochemistry and quadruple immunofluorescence performed on muscle biopsies showed normal function and subunit protein abundance of the complexes within the OXPHOS system. Our findings suggest that there is no primary mitochondrial OXPHOS dysfunction but raises the possibility of impaired oxygen delivery to the mitochondria affecting skeletal muscle bioenergetics during exercise.